Highly Integrated Organic–Inorganic Hybrid Architectures by Noncovalent Exfoliation of Graphite and Assembly with Zinc Oxide Nanoparticles. Issue 20 (7th October 2016) - Marcia, Mario; Vinh, Chau; Dolle, Christian; Abellán, Gonzalo; Schönamsgruber, Jörg; Schunk, Torsten; Butz, Benjamin; Spiecker, Erdmann; Hauke, Frank; Hirsch, Andreas
Abstract : Liquid‐phase exfoliated few‐layer graphene flakes are noncovalently functionalized with tailor‐made cationic water‐soluble perylene diimides. By using a straightforward dip‐coating approach, homogeneous ultrathin films consisting of interpenetrated nanoarchitectures can be achieved by incorporation of anionic ZnO nanoparticles. These 0D/2D assemblies pave the way for the development of novel graphene‐based composite materials.